Plasmablastic lymphoma of the oral cavity in an undiagnosed HIV‐positive patient. (8th January 2015) - Tabbenor, O.; Halai, T.; Bailey, E.; Coulthard, P.
Abstract Plasmablastic lymphoma is an HIV‐associated non‐Hodgkin's lymphoma that has a known effect on the oral cavity and jaws. A case is presented of oral plasmablastic lymphoma in an apparently medically well 38 year old male. The patient presented with a large mass fungating from the upper left second molar socket, 2 weeks following extraction. The presence of an exophytic soft tissue lesion in a socket shortly after extraction is an infrequent occurrence. Such lesions should be investigated appropriately as malignant lesions may clinically mimic the appearance of benign lesions.